Refugees, Economic Capacity, and Host State Repression*. Issue 1 (2nd January 2018) - Wright, Thorin M.; Moorthy, Shweta
Abstract: Does hosting refugees affect state repression? While there have been numerous studies that examine the link between refugees and the spread of civil and international conflict, an examination of the systematic links between refugees and repression is lacking. We contend that researchers are missing a crucial link, as the dissent-repression nexus is crucial to understanding the development of armed conflict. Drawing upon logics of the relationship between refugees and the spread of conflict as well as economic capacity, we argue that increased numbers of refugees lead to increased repression. We contend that willingness to increase repression when hosting refugees is in part conditional on a host state's economic capacity. We argue that, on the whole, the greater the population of refugees in a host state, repression becomes more likely. That said, we argue that increased economic capacity will moderate this relationship. We find empirical support for both predictions.